Recombinant Strains of Human Parechovirus in Rural Areas in the North of Brazil - Élcio Leal; Adriana Luchs; Flávio Augusto de Pádua Milagres; Shirley Vasconcelos Komninakis; Danielle Elise Gill; Márcia Cristina Alves Brito Sayão Lobato; Rafael Brustulin; Rogério Togisaki das Chagas; Maria de Fátima Neves dos Santos Abrão; Cássia Vitória de Deus Alves Soares; Fabiola Villanova; Steven S. Witkin; et al. (Viruses, 2019)
We characterized the 24 nearly full-length genomes of human parechoviruses (PeV) from children in the north of Brazil. The initial phylogenetic analysis indicated that 17 strains belonged to genotype 1, 5 to genotype 4, and 1 to genotype 17. A more detailed analysis revealed a high frequency of recombinant strains (58%): A total of 14 of our PeV-As were chimeric, with four distinct recombination patterns identified. Five strains were composed of genotypes 1 and 5 (Rec1/5); five strains shared a complex mosaic pattern formed by genotypes 4, 5, and 17 (Rec4/17/5); two strains were composed of genotypes 1 and 17 (Rec1/17); and two strains were composed of genotype 1 and an undetermined strain (Rec1/und). Coalescent analysis based on the Vp1 gene, which is free of recombination, indicated that the recombinant strains most likely arose in this region approximately 30 years ago. They are present in high frequencies and are circulating in different small and isolated cities in the state of Tocantins. Further studies will be needed to establish whether the detected recombinant strains have been replacing parental strains or if they are co-circulating in distinct frequencies in Tocantins.